Disease Burden and Treatment Patterns of Psoriasis in Russia: A Real-World Patient and Dermatologist Survey - Alexey A. Kubanov; Andrey L. Bakulev; Tatiana V. Fitileva; Evgenia Novoderezhkina; Isabelle Gilloteau; Haijun Tian; Tanya Howe; Guilhem Pietri (Adis, Springer Healthcare, 2018)
Abstract Introduction Data regarding disease burden and quality of life (QoL) for patients with psoriasis from Russia are limited. The objective of this study was to describe the demographic and clinical characteristics, comorbidities, and treatment patterns of systemic therapy eligible psoriasis patients in Russia in order to assess the impact of psoriasis on the QoL and work productivity of the patients and to evaluate patient/dermatologist concordance on disease severity, signs/symptoms, and satisfaction with psoriasis treatment. Methods Data were collected by the Growth from Knowledge Disease Atlas global real-world evidence programme from nine countries. The data from the Russian population are presented here. Adult patients who had a current or prior history of moderate-to-severe psoriasis and were receiving prescription treatment at the time of the survey were included. Dermatologist-reported data on disease severity, symptoms, comorbidities, and treatment as well as patient-reported data on QoL and work productivity were collected. Descriptive analysis of the data was conducted. Patient/dermatologist concordance was assessed using Cohen's κ. Results A total of 300 patients from Russia were included. The mean Psoriasis Area and Severity Index score was 9.0 and the mean disease duration was 9.9 years. The proportion of patients with itch, skin pain, and comorbidities increased as current psoriasis severity increased. The disease had a negative impact on patients' QoL (mean Dermatology Life Quality Index score: 7.1) and work productivity (33.2% drop in work productivity), which further deteriorated as disease severity increased. A large proportion of the enrolled patients (60%) were treated with topical agents only. Overall, the level of concordance between patients and their dermatologists regarding psoriasis severity and satisfaction with overall disease control achieved was low. Conclusion Results demonstrate a substantial disease burden on psoriasis patients in Russia, despite receiving treatment for their psoriasis, as well as low patient/dermatologist concordance of views on treatment outcomes. These findings also highlight a need to further incorporate the patient's views into treatment decision-making in Russia. Funding Novartis Pharma AG, Basel, Switzerland.